2009
DOI: 10.1016/j.jecp.2008.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Aligning body and world: Stable reference frames improve young children’s search for hidden objects

Abstract: This study investigated how young children's increasingly flexible use of spatial reference frames enables accurate search for hidden objects by using a task that 3-year-olds have been shown to perform with great accuracy and 2-year-olds have been shown to perform inaccurately. Children watched as an object was rolled down a ramp, behind a panel of doors, and stopped at a barrier visible above the doors. In two experiments, we gave 2 and 2.5-year-olds a strong reference frame by increasing the relative salienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…To explore the potential origins of relative object weight in young children’s reasoning about object motion, Perry et al’s (2008) study seems most pertinent. Here, they employed an apparatus with a slope and barrier, and found that toddlers frequently searched for objects released down the slope in a location beyond the barrier; a finding also noted by various other studies employing the same apparatus or simplified versions of it (Berthier, DeBlois, Poirier, Novak, & Clifton, 2000; Butler, Berthier, & Clifton, 2002; Gresham, 2012; Hood, Carey, & Prasada, 2000; Keen et al, 2008; Kloos, Haddad, & Keen, 2006; Mash, Keen, & Berthier, 2003; Mash, Novak, Berthier, & Keen, 2006; Perry, Samuelson, & Spencer, 2009).…”
Section: Introductionsupporting
confidence: 57%
See 1 more Smart Citation
“…To explore the potential origins of relative object weight in young children’s reasoning about object motion, Perry et al’s (2008) study seems most pertinent. Here, they employed an apparatus with a slope and barrier, and found that toddlers frequently searched for objects released down the slope in a location beyond the barrier; a finding also noted by various other studies employing the same apparatus or simplified versions of it (Berthier, DeBlois, Poirier, Novak, & Clifton, 2000; Butler, Berthier, & Clifton, 2002; Gresham, 2012; Hood, Carey, & Prasada, 2000; Keen et al, 2008; Kloos, Haddad, & Keen, 2006; Mash, Keen, & Berthier, 2003; Mash, Novak, Berthier, & Keen, 2006; Perry, Samuelson, & Spencer, 2009).…”
Section: Introductionsupporting
confidence: 57%
“…In line with other studies in the field examining relevant hidden displacement tasks using the same apparatus (cf. Berthier et al, 2000; Butler et al, 2002; Gresham, 2012; Keen et al, 2008; Kloos et al, 2006; Mash et al, 2003, 2006; Perry et al, 2008, 2009), toddlers’ search successes generally increased with age. Disregarding any differences between conditions, the youngest children in the present study merely performed at chance level as a whole, but by the age of 3 years they were already correct in around two-thirds of their searches.…”
Section: Discussionmentioning
confidence: 98%
“…However, failure can tell us something more interesting about development (Keen, 2003 ; Perry et al, 2008 , 2009 ). For example, Perry et al ( 2009 ) demonstrated changes in children's ability to align their body and movements with relevant spatial reference frames support search accuracy.…”
Section: A Temptation Of Lookingmentioning
confidence: 99%
“…However, failure can tell us something more interesting about development (Keen, 2003 ; Perry et al, 2008 , 2009 ). For example, Perry et al ( 2009 ) demonstrated changes in children's ability to align their body and movements with relevant spatial reference frames support search accuracy. When 2-year-olds underwent training with the barrier in a fixed position while the ramp moved, such that the correct door was aligned with midline, they correctly located the object during the standard testing procedure.…”
Section: A Temptation Of Lookingmentioning
confidence: 99%